Research on regionization of ecological environment types and its construction in Zhejiang province - WU Guo-qing; YANG Liang-shan (浙江大学学报. 农业与生命科学版)
Based on the principle of entirety of ecological systems and the ideas of combining qualitative methods with quantitative ones, combining natural factors with social and economic ones, combining regionization with classification, The authors build factors of classification and regionizes the types of the ecological environment in Zhejiang province, applied with the AHP, leading factors analysis, comprehensive evaluation, and Delephi etc. The main problems and construction countermeasures of ecological environment in key regions are discussed.